2020
DOI: 10.33221/jiiki.v10i04.811
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Program Pemberdayaan Keluarga Sebagai Upaya Meningkatkan Status Fungsional Klien dan Kesiapan Keluarga Merawat Klien Stroke

Abstract: Pendahuluan: Stroke merupakan kondisi hilangnya fungsi otak karena gangguan aliran darah otak terjadi lebih dari 24 jam. Stroke berdampak fisik maupun mental sehingga klien stroke bergantung kepada keluarga serta membutuhkan perawatan dan pemulihan jangka panjang. Tujuan: Tujuan penelitian untuk mengetahui pengaruh program pemberdayaan keluarga terhadap status fungsional klien dan kesiapan keluarga merawat klien stroke. Metode: Desain penelitian quasi experiment dengan pendekatan control group pret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
2
1
0
1
Order By: Relevance
“…These results also support the findings of Arista et al (2020) where there is an influence of the implementation of family empowerment programs on family readiness to care for stroke clients (p value 0.004 < 0.05). Family empowerment programs in preparation for return plans have a positive impact on family readiness to care for stroke clients.…”
Section: Bivariate Analysissupporting
confidence: 88%
See 1 more Smart Citation
“…These results also support the findings of Arista et al (2020) where there is an influence of the implementation of family empowerment programs on family readiness to care for stroke clients (p value 0.004 < 0.05). Family empowerment programs in preparation for return plans have a positive impact on family readiness to care for stroke clients.…”
Section: Bivariate Analysissupporting
confidence: 88%
“…for post-stroke patients felt ready (87.5%). The results of this study are supported by research found by Arista et al (2020) in their research where after the family is given health education, it is able to improve its ability to care for stroke patients so that they have higher readiness in caring for post-stroke patients. Health education provided must be continuous, which not only focuses on delivering knowledge but also motivates and encourages clients to participate in facing problems related to disease, including changing a healthy lifestyle and in obtaining final results as expected.…”
Section: Bivariate Analysissupporting
confidence: 74%
“…Through these roles, nurses not only assist in the physical recovery process for post-stroke patients but also play a central role in enhancing the quality of life and supporting patients in facing the challenges resulting from stroke (Meng et al, 2020). Patients with post-stroke often experience a decrease in swallowing ability as a result of stroke attacks that occur in the blood vessels of their brain and have a fairly high incidence rate in adults and the elderly (Arista, Nurachmah, & Herawati, 2020). In addition, post-stroke patients also often experience impaired motor function, namely dysphagia.…”
Section: Introductionmentioning
confidence: 99%
“…Stroke hemoragik adalah stroke yg terjadi ketika pembuluh darah di otak pecah dan menyebabkan pendarahan di otak. Gejala stroke dapat bervariasi tergantung pada jenis dan tingkat keparahan stroke, tetapi gejala umumnya termasuk kelemahan atau mati rasa yang tiba-tiba di wajah, lengan, atau kaki, kesulitan berbicara atau memahami ucapan, dan masalah penglihatan mendadak (Arista et al, 2020).…”
unclassified